Low‐head pumped hydro storage: An evaluation of energy balancing and frequency support - Justus Peter Hoffstaedt; Daan Truijen; Antonio Jarquin Laguna; Jeroen De Kooning; Kurt Stockman; Jonathan Fahlbeck; Hakan Nilsson (IET Renewable Power Generation)
Abstract Large‐scale energy storage solutions are crucial to ensure grid stability and reliability in the ongoing energy transition towards a low‐carbon, renewable energy based electricity supply. This article presents the evaluation of a novel low‐head pumped hydro storage system designed for coastal environments and shallow seas. The proposed system addresses some of the challenges of low‐head pumped hydro storage including the need for larger flow rates and reservoirs as well as the requirement of machinery with high efficiencies across a wide operating range to accommodate larger changes in gross head during storage cycles. It includes several units of contra‐rotating reversible pump‐turbines connected to axial‐flux motor generators within a ring dike, as well as dedicated machine‐ and grid‐side control. The technology allows for independent control of each runner, making it possible to adapt to the specific operating conditions of low‐head systems. In this work, a numerical approach is used to simulate the system's performance and dynamic behaviour under various operational conditions, including energy generation, storage, and grid support of a 1 GW system with 4 GWh of storage capacity. The potential system performance for energy balancing cycles is evaluated, and a sensitivity analysis is conducted to assess the influence of scaling the motor‐generators on performance and footprint of the plant. Additionally, the capability and limitations of the system to respond to grid demand fluctuations and provide frequency regulation services are assessed. The results demonstrate that the low‐head pumped hydro storage system is a viable large‐scale energy storage solution, capable of round‐trip efficiencies above 70% across a wide operating range. By increasing the maximum power of the electric machines, the maximum head range of the whole system is increased which correlates with a threefold increase in energy density per unit area. The dynamic simulations further show that the system can rapidly change its power output allowing it to provide frequency regulation services. Allocating 20% of its nominal power as a reserve, the new power setpoints can be reached within a maximum of 5 s independent of its initial state of charge.